FRUGIVOROUS FLIES (Diptera: Tephritidae and Lonchaeidae) INTERACTIONS WITH PARASITOIDS AND NEW HOSTS - Louzeiro, Léo R. F.; Raga, Adalton; Souza-Filho, Miguel F. de; Gisloti, Laura J. (REVISTA DE AGRICULTURA, 2021)
Fruits of two cultivars of guava, Psidium guajava L., (‘Tailandesa’ and ‘Kumagai’) and garlic passion fruit, Passiflora tenuifila Killip were collected to evaluate the infestation and co-infestation of frugivorous flies and the associated parasitoids and new hosts. Five species of Tephritoidea were recovered in Tailandesa guavas, three species in Kumagai guavas and three species in garlic passion fruit. This is the first report of a frugivorous fly infesting P. tenuifila. Individualization of the fruit samples was used to determine the co-infestation between Anastrepha spp., Ceratitis capitata and Neosilba spp. in each fruit. There was a fly/parasitoid association for Doryctobracon areolatus and Lopheucoila anastrephae with Anastrepha fraterculus in guavas. Infestation indices and emergence rate demonstrated that Tailandesa and Kumagai guavas are hosts capable of withstanding an infestation index ≥ 50 pupae/fruit and have an emergence rate ≥ 75%. The ability of some hosts to maintain and sustain the population of frugivorous flies at high levels may interfere with pest management.